Characteristics of better performing manufacturing companies in new product development success - Wan Jusoh, Wan jamaliah (2012)

(untitled)
The contribution of new products to corporate growth and survival has long been acknowledged. However, not much is known about the differences in characteristics of better performing compared to lesser performing companies in new product development. Therefore, it is the aim of this study to investigate the characteristics of better performing companies compared to lesser performing companies in successful new product development.